Macroeconomic uncertainty in South East Asia: a comparative study between Malaysia and Indonesia - Chow, Yee Peng; Muhammad, Junaina; Amin Noordin, Bany Ariffin; Cheng, Fan Fah (Macrothink Institute, 2017)
This paper examines the historical pattern of macroeconomic uncertainty of two developing countries in the South East Asia, namely Malaysia and Indonesia. Comparisons of macroeconomic uncertainty are also made between both countries using a selected number of indicators for macroeconomic volatility. We find that while both countries were affected by similar external sources of macroeconomic uncertainty, these countries were also subject to domestic sources of macroeconomic uncertainty which were confined to the particular country. The analyses also reveal that Indonesia experienced more fluctuations compared to Malaysia when macroeconomic uncertainty is measured by volatility as a macroeconomic outcome and domestic sources of macroeconomic volatility. Contrarily, Malaysia displayed greater fluctuations than Indonesia when macroeconomic uncertainty is measured by external sources of macroeconomic volatility. Policy implications are drawn from the findings.